The value of remote care in the reduction of healthcare utilization in implantable cardioverter‐defibrillator patients. Issue 12 (16th November 2021) - van Steenbergen, Gijs; Ben Jaddi, Oumaima; Theuns, Dominic; van Veghel, Dennis; Dekker, Lukas; Simmers, Tim
Abstract: Background: Minimal evidence is available of the reduction in healthcare utilization of remote care in ICD patients over a longer period of follow‐up. Objectives: This study compared healthcare utilization up to 3 year follow‐up in implantable cardioverter‐defibrillator (ICD) patients with remote care compared to conventional care. Methods: We conducted a retrospective cohort study of patients who received a single or dual‐chamber ICD or cardiac resynchronization therapy‐defibrillator (CRT‐D) between 2016 and 2018. Patients with remote care and patients were compared with patients with received conventional care (control group). The primary endpoint was a composite of cardiac follow‐up visits, ICD follow‐up visits, telephone consultations, emergency department (ED) visits and hospital admissions and was defined as total healthcare utilization. The secondary endpoints were the individual care activities and one‐year all‐cause mortality. Results: A total of 497 patients were included in the study, of which 299 patients were allocated to the remote care and 198 patients to the control group. Mean follow‐up was 815 ± 279 days. Remote care was associated with a significantly lower rate of adjusted total healthcare utilization in comparison to the control group that sustained for 3 subsequent follow‐up years (IRR = 0.78, 95% CI [0.67 to 0.92], p  < .01). One‐year all‐cause mortality was similar between the remote care and control group (respectively 3.0% vs. 5.5%, p  = .29). Conclusions: Compared to the standard follow‐up of in‐office care, a remote care program was associated with a sustained lower rate of planned and unplanned healthcare utilization up to 3 subsequent years after ICD/CRT‐D implantation.